Cognitive reappraisal improves the social decision-making performance of suicide attempters - Tong Wang; Xiaoya Liu; Moxin Duan; Bo Zhang; Li An; Shuang Liu; Dong Ming (Fundamental Research)
A growing body of evidence suggests that emotion regulation (ER) plays a crucial role in the decision-making (DM) process of suicide attempters (SA). Cognitive reappraisal (CR), an emotion regulation strategy that reinterprets emotional situations to alter physiological and emotional responses, has been studied widely. Whereas, its effect on SA is yet to be explored. The present study attempted to use CR to modulate ER in SA to improve their DM performance, and explore the physiological mechanisms underlying this process. Scale scores under natural responses and after using the CR strategy, as well as behavioral and electroencephalographic (EEG) data from subjects were recorded during the classical DM task - ultimatum game (UG) paradigm. 52 patients with psychiatric disorders (including 26 SA and 26 non-suicide attempters) and 22 healthy controls (HC) performed in UG. Scale results showed that negative emotional experience scores decreased in all three groups after CR, but SA showed less improvement compared to HC. The behavioral results showed that acceptance of SA significantly increased after CR in both fair and unfair alternatives in the UG task, suggesting that CR can improve DM performance of SA. Besides, we extracted the late-positive potential (LPP) and theta-gamma coupling (TGC) of EEG for analysis. The LPP of SA was significantly higher when facing unfair alternatives than in fair ones, reflecting the fact that SA showed stronger negative emotions in the face of unfair situations. In addition, SA exhibited TGC diminished in frontotemporal regions when facing unfair allocation schemes, which demonstrated the existence of cognitive impairment in SA. This study verified the feasibility of CR for the moderation of DM ability in SA and provided new ideas for early intervention of suicidal behavior.